In This Issue - David Briggs (ACHSM, 2021)
This issue of the journal commences with an editorial that provides some discussion about the current approaches to Covid and the tensions that exists in that context..... Editorial SettingsCovid-19: A strife of interests for us all and what problem are we attempting to solve? Research Articles Gender Equity in Australian Health Leadership Research Articles Assessing Quality of Healthcare Delivery When Making Choices: National Survey on Health Consumers' Decision Making Practices Research Articles The Case for a Reciprocal Health Care Agreement between Australia and South Korea Commentary COVID-19 and Working Within Health Care Systems: the future is flexible Review Articles Review of Public Private Partnership in the Health Care in Hong Kong Viewpoint Article Hong Kong's Growing Need for Palliative Care Services and the Role of the Nursing Profession Commentary Vietnam's Healthcare System Decentralization: how well does it respond to global health crises such as covid-19 pandemic? Research Articles Publicly Financed Health Insurance Schemes and Horizontal Inequity in Inpatient Service Use in India Research Articles Distress and Quality of Life among Type II Diabetic Patients: Role of physical activity Viewpoint Article Achievements and Challenges of Iran Health System after Islamic Revolution: Structural reforms at the second step Research Articles Strategic Analysis of Community Participation in Primary Health Care in Iran and Presentation of Promotion Strategies Using Internal and External Environment Assessment Techniques Research Articles Utilization of Healthcare Services & Healthcare Expenditure Patterns in the Rural Households of Nepal